Nudging Enforcers: How Norm Perceptions and Motives for Lying Shape Sanctions - Eugen Dimant; Tobias Gesche (Center for Economic Studies and ifo Institute (CESifo), 2021)
The enforcement of social norms is the fabric of a functioning society. Through the lens of mul-tiple studies using different methodologies (a behavioral experiment and a vignette experiment in Study 1, as well as a norm elicitation experiment in Study 2), we examine how motives for lying and norm perceptions steer norm enforcement. Pursuing a pre-registered three-part data collection effort, our study investigates the extent to which norm breaches are sanctioned, how norm-nudges affect punishment behavior, and how enforcement links to norm perceptions. Using a representative sample of U.S. participants, we provide robust evidence that norm-enforcement is not only sensitive to the magnitude of the observed transgression (= size of the lie) but also to the consequence of the transgression (= whether the lie remedies or creates payoff inequalities). We also find that norm enforcers are sensitive to different norm-nudges that convey social in-formation about actual lying behavior or its social disapproval. Importantly, these results hold both in the behavioral experiment and in an add-on vignette study that confirm the robustness of our findings in the context of whistleblowing. To explain the punishment patterns of the behavioral experiment in Study 1, we subsequently examine how norms are perceived across dif-ferent transgressions and how norm-nudges change these perceptions. We find that social norm perceptions are malleable: norm-nudges are most effective when preexisting norms are vague. Importantly, we find that punishment patterns in the first experiment closely follow these norm perceptions. With that, our findings suggest that norm enforcement can be nudged successfully.
Keywords: B41; D01; D90; 330; lying; norm-nudges; nudging; punishment; social norms